FACTORS INFLUENCING THE UTILISATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES (ICTs) AMONG RICE FARMERS IN BAUCHI STATE, NIGERIA - Babuga, U. S.; Murtala, N.; Abdullahi, S.; Jibril, S. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the factors influencing the utilisation of information and communication technologies (ICTs) among rice farmers in Bauchi State, Nigeria. Multi-stage sampling techniques was used in selecting 433 respondents. Data were collected using structured questionnaires and analyzed using both descriptive and inferential statistics. The results revealed that more than half (54.3%) of the respondents had low knowledge of ICTs, while 45.7% had medium knowledge. The results also disclosed that 53.1% of the respondents utilized ICTs at medium level while 46.7% and 0.2% used it at low and high level. The results further revealed majority (58.2%) of the respondents used mobile phones most frequently on daily basis. Majority (74.4%) used ICTs to learn about new farming techniques while 74.1% and 73.4% use it in communication with other rmers and accessing market information). The results of regression analysis revealed that household size (P<0.05), educational level (P<0.01), farming experience (P<0.05), membership of cooperatives (P<0.05), access and frequency of extension contacts (P<0.01) were the factors influencing the level of utilisation of ICTs. The results of t-test statistic for rice output (t = 26.470; P< 0.01) indicate a strong, positive and significant relationship between the rice output and ICT utilization in the study area. The major constraint to effective utilization of ICTs were high cost of ICT devices and maintenance (75.1%), poor internet connectivity (73.5%). erratic power supply (71.6%) and high cost of internet subscription (71.1%) which were ranked 1st, 2nd, 3rd and 4th, respectively. The study concluded that household size, educational level, farming experience, membership of cooperatives, access and frequency of extension contacts, were the significant factors influencing the utilization of ICTs among rice farmers in the study area. The study recommended that government and development partners should subsidize ICT devices for farmers and promote affordable maintenance services to enhance accessibility, ICT platforms should be developed with localized, user-friendly content in local languages to ensure that farmers receive information relevant to their needs and ICT companies should provide affordable repair services and reliable after-sales support.